The impact of transformational leadership behaviors on work performance of Omani civil service agencies - Al Kindy, A. M. Z. (Canadian Center of Science and Education, 2016)
In line with the Recommendations of the Symposium of Development of Governmental Performance (Ministry of Civil Services, 2012), this study is investigating the behavior of the Omani Civil Service Agencies’ (OCSA) middle managers Transformational Leadership behaviors in enhancing task and contextual behavior work performance. A review of the literature revealed that there is a positive relationship between transformational leadership behaviors and work performance behaviors. However, there is limited number of studies investigating this relationship in Oman generally and specifically in the public sector. The results are expected to show that the transformational leadership behaviors have a positive relationship with task and contextual work performance behaviors of OCSA.